Women’s Articles in National English Dailies: Coverage Priority and Issues Diversity - Aryal, Shobha; Karki, Arjun (International Journal of Social Sciences and Management, 2022)
Name of first author is corrected as Shobha Aryal, by mistake it was written Shova Aryal. This study explores diversities, issues and priorities of women's articles in four broadsheet dailies in Nepal. The study has analyzed the ratio of national and foreign writers. It shoves into the number of women's writers and their areas/issues of writing. The study employs a content analysis research approach. It has extracted 351 articles of one month each national dailies of the year 2018. The articles have been encoded into appropriate fields and grouped under the eight different fields/areas. Then an analysis has been made on gender, issues, priorities and diversities of the articles. The findings are different in each newspaper. The Himalayan Times daily has been found more inclusive in terms of areas and gender priorities. The Kathmandu Post daily has been found to have been given least priority to national writers, regardless of women's writing. Similarly, the finding showed the largest variations in the Kathmandu Post in gender, issues and coverage. The Rising Nepal is found to have given more priority to national writers. Finally, the Republica daily has the second largest variations after the Kathmandu Post; however, the areas of writing have a great discrepancy. This study recommends for the positive discrimination to the women as stated in the gender related policies. The government, media and other stakeholders should play the facilitating role to monitor the media organizations for gender inclusivity in all the areas of work. Future studies focus on the wages, work flexibilities and responsibilities in media to promote peace, prosperity and holistic development of the nation. Int. J. Soc. Sc. Manage. Vol. 9, Issue-1: 27-40.